2020
DOI: 10.1016/j.leaqua.2019.101377
|View full text |Cite
|
Sign up to set email alerts
|

Leading teams in the digital age: Four perspectives on technology and what they mean for leading teams

Abstract: Digital technologies are changing the nature of teamwork in ways that have important implications for leadership. Though conceptually rich and multi-disciplinary, much of the burgeoning work on technology has not been fully integrated into the leadership literature. To fill this gap, we organize existing work on leadership and technology, outlining four perspectives: (1) technology as context, (2) technology as sociomaterial, (3) technology as creation medium, and (4) technology as teammate. Each technology pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
134
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(173 citation statements)
references
References 149 publications
0
134
0
7
Order By: Relevance
“…As we've discussed, different mediums of communication involve varying degrees of virtuality and therefore information content. Intentionally thinking about the benefits and detriments of a communication medium before using it at least improves employee awareness of repercussions, and at best increases shared understanding and communicative efficiency (Gibbs et al, 2017;Larson and DeChurch, 2020;Martins et al, 2004). How likely are the parties to understand one another?…”
Section: Communicate Intentionallymentioning
confidence: 99%
See 2 more Smart Citations
“…As we've discussed, different mediums of communication involve varying degrees of virtuality and therefore information content. Intentionally thinking about the benefits and detriments of a communication medium before using it at least improves employee awareness of repercussions, and at best increases shared understanding and communicative efficiency (Gibbs et al, 2017;Larson and DeChurch, 2020;Martins et al, 2004). How likely are the parties to understand one another?…”
Section: Communicate Intentionallymentioning
confidence: 99%
“…However, the increasing complexity of projects often means that small teams are insufficient for the parallel completion of tasks necessary to complete a project on time. In larger virtual teams, sharing leadership responsibilities among team members improves performance by decreasing delays introduced by managerial inputs and oversight, especially in highly-skilled teams (Hoch and Kozlowski, 2014;Schaubroeck and Yu, 2017;Gibbs et al, 2017;Larson and DeChurch, 2020).…”
Section: Reduce Coordination Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…The players and club staff had to quickly adjust from a context of close and regular face-to-face interaction to virtual interaction via technology as context for leadership and teamwork. Larson and DeChurch (2020) reviewed the literature on technology and leadership and determined that (a) the technology used influences the leadership practice in teams and (b) sharing leadership is beneficial for team leadership.…”
Section: Staying In Contactmentioning
confidence: 99%
“…Using Zoom (video and audio) as a platform to conduct group training sessions facilitates interaction between group members, as opposed to other options that could involve players completing prescribed workouts on their own, thus not having the opportunity to practice leadership through interaction (Larson & DeChurch, 2020). The players indicated that the virtual presence of their teammates and coaches has allowed them to feel motivated and connected, an experience Player 1 sometimes lacks when doing self-workouts: "when I do a session by myself it is quite lonely : : : but with the computer screen, you randomly have people talking to you, it feels like you are actually with people."…”
Section: Staying In Contactmentioning
confidence: 99%